Analisis Posisi Pasar Produk Pasta Gigi Berdasarkan Persepsi Konsumen - Silvia Diva Sari; Annisa Muty Nur Ami; Cindy Dwiana Putri; Lenti Susana Saragih (Pusat Riset dan Inovasi Nasional, 2023)
The aim of the author in conducting this research is to analyze and study the positioning or market position of Pepsodent, Ciptadent and Close up brand toothpaste products based on consumer perceptions. This research uses a descriptive qualitative method with a literature study method. In general, Pepsodent, Ciptadent and Close-up toothpastes have the main characteristics of their contents. Pepsodent is the superior choice in terms of packaging size, while Ciptadent stands out in the attributes of taste, color, content, product design and packaging design. Close Up has similarities in terms of packaging attributes to Pepsodent